(untitled) (Fiep Bulletin - online, 2016)
This research deals and reflected on core issues of play in early childhood education in the light of psychoanalysis, highlighting them as resources and important tools for the development of children. It sought for through this, understand and understand the benefits of using recreational activities and play in the kindergarten school, analyzing and reflecting on the theories related to the use of playfulness in this environment, comparing them with the pedagogical practices carried out by teachers Children’s education in a municipal school in the city of Tan-PB, observing since the natural play of the child is very significant to their learning, their development, as well as for access to the unconscious child by psychoanalytic technique. In this sense, the play is the very life of the child, through which it can move, express themselves and develop. The method used was qualitative descriptive field research, in which we as a tool for data collection, interviews were conducted and compiled from the proposed objectives, presenting questions, open and closed, applied to the subject: (10) ten teachers infantildiscutindo teaching about the use and importance of the play in early childhood education. After analyzing the data, we observed that although they consider important recreational activities, are not all that use them as a teaching tool in the classroom. And, although the professionals questioned have a good level of education does not mean it is fully prepared to deal with the playfulness in their teaching as it lacks a playful training and total gift that requires early childhood education. So it’s extremely important the use of playful educational practice, not only for learning and student development, but also for the teacher. Thus, when used from recreational use, either by playing or the game, he will be contributing not only to the development of learning and the child’s potential, but also enable numerous relationships between thought and reality. So psychoanalysis as a theory of development and knowledge of the psychic apparatus, brings a new way of looking at the child and shows that, through play we can understand their behavior, their troubles and know how in reality it is because playing it expresses its inner reality.